1993
DOI: 10.1111/j.1600-0625.1993.tb00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the etiopathomechanism of vitiligo: A convergence theory

Abstract: Vitiligo is an acquired melanin pigmentary disorder manifesting itself by expanding depigmented lesions of the skin. To date, the etiopathomechanism of vitiligo has not been convincingly elucidated and a number of seemingly mutually opposed hypotheses with equal likelihood still coexist. Concurrent theories on vitiligo etiology, together with supportive evidence, are reviewed here. Due to the observed variation in clinical manifestations of the disease, it seems likely that the etiology of vitiligo may differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
202
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(208 citation statements)
references
References 72 publications
2
202
0
4
Order By: Relevance
“…138 The aetiology of the disease is mainly unknown, but autoimmunity is likely to be involved. 139 Autoantibodies against tyrosinase 140,142 and tyrosinase-related protein-2 143 have been demonstrated in patients with vitiligo. Several studies have reported associations of vitiligo with certain HLA specificities, but no consistent association with any of the HLA class I or class II alleles has been reported.…”
Section: Vitiligomentioning
confidence: 99%
“…138 The aetiology of the disease is mainly unknown, but autoimmunity is likely to be involved. 139 Autoantibodies against tyrosinase 140,142 and tyrosinase-related protein-2 143 have been demonstrated in patients with vitiligo. Several studies have reported associations of vitiligo with certain HLA specificities, but no consistent association with any of the HLA class I or class II alleles has been reported.…”
Section: Vitiligomentioning
confidence: 99%
“…Several studies prove the presence of oxidative stress and the accumulation of free radicals in the epidermal layer of affected skin, and recently antioxidant enzymes and lipid peroxidation have been detected in the tissues of vitiligo patients [2,4]. Le Poole et al in 1993 worked out the ''convergence theory'', which suggests the synergistic role of all the above-mentioned factors and cells in the pathogenesis of vitiligo [9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A convergence theory combining all these pathogenetic hypotheses has also been suggested. 5 In the majority of patients with vitiligo, the diagnosis is established by direct clinical inspection followed by examination of the depigmented areas under Wood light. Therefore, there are only a few reports on histopathological changes in vitiligo.…”
Section: Introductionmentioning
confidence: 99%